Acoustic radiation force in standing and quasi-standing high-order Bessel beams on a multilayered sphere - Yuchen Zang; Weijun Lin (Results in Physics, 2020)
The acoustic radiation force exerted by a standing and quasi-standing high-order Bessel beam on a multilayered sphere immersed in an ideal fluid is theoretically and numerically studied in this work. By means of the finite series method, the incident beam is expanded in terms of spherical harmonic functions. An analytical expression of the acoustic radiation force is derived based on the sound scattering theory. The dimensionless radiation force function versus ka is also simulated, with a particular emphasis on the relative thickness of each layer as well as the half-cone angle. To better simulate the practical manipulation, the effect of sound absorption is also analyzed. The simulated results of the first three orders reveal that the radius of each layer affects the position of peaks and dips of the curves, and acoustic trapping can be achieved at selected ka. It is also found that the curves exhibit the same general trend but the opposite directions when the order is 1 and 2, respectively. This study is expected to be useful in acoustic manipulation, drug delivery in the field of biomedical ultrasound and material sciences.